The Evaluation of the Real Exchange Rate of the Litas - Kropienė, Rūta (Ekonomika, 1998)
The competitiveness of country is.a multi-dimensional term and it is impossible to describe it adequately on the macroeconomic level by the single quantity. In the present article we describe the methods of evaluating the real effective exchange rate index (REER) by using consumer price index (CPI). The real effective exchange rate index is calculated as a weighted average of the individual bilateral exchange rate indices.The calculation involves a number of technical problems. below, we will study only a few of them: the choice between the arithmetical and geometrical weighted average; defining the weights; the content of the weights basket and its change in time; and the choice of the price change indicator. The article also describes how these problems have been dealt with at the Bank of Lithuania when calculating the real effective exchange rate of the Litas. Some empirical results have also been presented.